Central Airway Stenting as a Palliative Procedure in A Patient with Critical Airway Stenosis - Isidro Fracasso, João; Dezordi Dall'Agnol, Amanda; Benincá Albuquerque, Antônio; Boeira Rovani, André Luca; Beltrame, Cássia; Baroni de Macedo, Guilherme; Priori, Leonardo; Branco Schweitzer Mendes, Nathalia; Teixeira Simon, Thiago; Buaes Dal Maso, Vinícius (International Journal of Innovative Research in Medical Science, 2024)
Stents are devices designed to maintain the patency of tubular structures. Airway stents are placed in the central tracheobronchial tree and used either for malignant obstruction or for benign diseases. Their use is indicated in both intrinsic obstruction or extrinsic compression of the airway. We present a case of a 60-year-old female patient with an extrinsic mass obstructing the tracheal lumen, presenting with progressive dyspnea at the slightest effort, in which a stent was successfully placed as a palliative procedure.